2013
DOI: 10.1126/scisignal.2003755
|View full text |Cite
|
Sign up to set email alerts
|

Mechanosensitive ATP Release Maintains Proper Mucus Hydration of Airways

Abstract: The clearance of mucus from the airways protects the lungs from inhaled noxious and infectious materials. Proper hydration of the mucus layer enables efficient mucus clearance through beating of cilia on airway epithelial cells, and reduced clearance of excessively concentrated mucus occurs in patients with chronic obstructive pulmonary disease and cystic fibrosis. Key steps in the mucus transport process are airway epithelia sensing and responding to changes in mucus hydration. We reported that extracellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
111
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(117 citation statements)
references
References 53 publications
6
111
0
Order By: Relevance
“…In general, measurements of CBF and MCT in this study were similar to values obtained in other studies of cultured HBE cells (6,25,29,38). For example, Matsui et al (29) reported mucus transport velocities of 20 -80 m/s, and Liu et al (25) reported a CBF of 9 -10 Hz in cultured HBE cells.…”
Section: Discussionsupporting
confidence: 89%
“…In general, measurements of CBF and MCT in this study were similar to values obtained in other studies of cultured HBE cells (6,25,29,38). For example, Matsui et al (29) reported mucus transport velocities of 20 -80 m/s, and Liu et al (25) reported a CBF of 9 -10 Hz in cultured HBE cells.…”
Section: Discussionsupporting
confidence: 89%
“…Normal lung function requires ATP release by AECs to optimize airway surface layer hydration, mucus composition, and mucociliary clearance (93). However, excessive ATP release from dying or damaged cells acts as a DAMP and is recognized by the purinergic receptor P2X7, which is expressed specifically on cells of the immune system and is involved in the release of IL-1β (94).…”
Section: Mtdampsmentioning
confidence: 99%
“…ADO was significant reduced in the subjects with CB as compared with the CS-N (P = 0.03). Because ATP and ADO are the two active nucleotides/nucleosides regulating airway surface liquid (ASL) volume and mucus concentration, the sum of ATP and ADO concentrations across groups was compared ( Figure 2B) (18,26). The combined ATP/ADO concentrations were significantly lower in the CB group (566 6 73 mM) than the NS control group (2,003 6 495 mM; P = 0.0006) or the CS-N group (1,588 6 355 mM; P = 0.02).…”
Section: Sputum Atp and Metabolite Concentrationsmentioning
confidence: 99%
“…Human airway epithelial cultures (HBE) were left unwashed for 2-3 weeks to produce mucus with greater than 10% solids (16,29). To measure MCC, fluorescent microspheres were added to the apical surface of HBE cultures approximately 16 hours before study (18,30). MCC rates were calculated from time-lapse fluorescent images (30).…”
Section: Measurement Of In Vitro Mucociliary Transport Ratesmentioning
confidence: 99%
See 1 more Smart Citation